Microbiology Managers: Managerial Training in the RItrain Project. Issue 6 (June 2017) - Paterson, R. Russell M.; Lima, Nelson; Brooksbank, Cath; Guarini, Enrico; Pasterk, Markus; Lavitrano, Marialuisa; ,
Abstract : Leaders of research infrastructures (RIs) in Europe who are scientists require competencies in management. RItrain has addressed this issue by identifying skills required, locating relevant courses and finding gaps, whilst establishing a Master of Management programme. We describe how one contributing microbiology RI determined the most relevant skills.